I can lick 30 tigers today : and other stories - Seuss, Dr. (New York : Random House, 1969)
Three stories in verse: "I Can Lick 30 Tigers Today," "King Looie Katz, " and "The Glunk That Got Thunk."
I can lick 30 tigers today! -- King Looie Katz -- The Glunk that got thunk.
Accelerated Reader AR
Reading Counts RC
108723
Keywords: Children's stories, American; Stories in rhyme; Animals - Lions, Tigers, Leopards, etc; Concepts - Counting & Numbers; JUVENILE FICTION / Humorous Stories; Children's stories, American; Humorous stories; Children's stories -- 1969.; Stories in rhyme; Juvenile works - Fiction